Spatial-Based Space Designation Factor Analysis of Rice Fields Conversion (Case Study: West Java Province) - Sukiptiyah Sukiptiyah; Ernan Rustiadi; Akhmad Fauzi; Baba Barus (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Regional economic development in the concept of spatial planning is based on cultivation areas, including the allocation of production forests, agriculture, mining, settlements, industry, tourism and trade. Economic development in rural areas is not only to improve welfare but also to fulfill food (rice) needs. One of the benchmarks for the level of welfare is the Gross Regional Domestic Product (GDP). Conversion of agricultural land into built-up land is a mechanism for regional economic development activities, where to increase GDP, allocate the widest possible allocation of industrial, trade and residential space which has implications for increasing conversion of agricultural land (rice fields) and reducing rice production facilities so that food fulfillment is constrained, in other words, there is a trade off in the use of agricultural land (rice fields). The purpose of this study was to analyze the distribution and conversion of paddy fields pattern in terms of space designation, road access and land prices, analyze the spatial designation factors affecting paddy field conversion and determine the priority scale of revision of Spatial Planning in terms of the potential for rice field conversion in rural areas. The research location is distinguished in rural areas with high and low industrialization and urbanization. Input data using spatial software with overlay technique and to answer the objectives using quantitative spatial analysis, multiple linear regression analysis and spatial multicriteria analysis of 4 (four) criteria (space allocation, road access, population density and land prices). The results showed that the distribution pattern of paddy fields according to road access was dominant in an area > 3 km from the road, followed by an area of 1-3 km from the road and the lowest in an area of 0-1 km from the road. The distribution of paddy fields according to the spatial designation is dominant with the designation of agricultural space-wetland, while the rice fields with the designation of space-residential, trade, industry is dominant in rural areas with high industrialization and urbanization. Conversion of paddy fields into built-up land is dominant in industrialized and urbanized highly rural areas, in the designation of space-residential, trade, industry and in areas 0-3 km from the road. The allocation of space for paddy fields can have an impact on encouraging or controlling land conversion, where rice fields with the designation of space-residential, trade, industry can encourage land conversion, on the other hand, rice fields with non-residential designation for industrial trade are relatively controllable. Revision of Spatial Planning is recommended in rural areas with relatively high potential for conversion of paddy fields, namely in rural areas with high industrialization and urbanization.